Menelusuri Makna Kata Nur dalam Al-Qur'an: Aplikasi Semantik Ensiklopedik - Rohman, Abdul; Irfan, Muhammad; Amin, Amin (Universitas Negeri Padang, 2023)
Many words in the Koran have many meanings. Likewise, vice versa, there are many different words but they have the same meaning. A comprehensive expression of meaning is needed to arrive at objective meaning. The purpose of this article is to reveal the meaning of the word nūr in the Qur'an. The method used is a qualitative method through a content analysis approach using encyclopedic semantic theory. The research results reveal that the word nūr in the Koran has many meanings. In pre-Quranic times, the word nūr meant the material of shining light and life. Meanwhile, during the era of the Qur'an, its meaning had expanded to include the material of light, the Qur'an, the prophet Muhammad, God's guidance, the explanation of laws, the light of faith, the light of justice, God's religion, reward, and revelation.